Analysis factors of Tourist Decisions’ on Melukat Tradition as a Spiritual Tourism - Hubertina Karolina Ngarbingan; Anisa Zahwa Akbara (UNIVED Press, 2024)
The creativity of the Balinese people who combined new tourism trends with Balinese traditions, a new habit was formed, namely Melukat tradition. Currently, Melukat tradition has become an interfaith tourism trend in Bali, many non-Hindu tourists believe in what Hindus believe, by following the procession of the Melukat tradition itself. This phenomenon are based on the data from visitors who follow the Melukat tradition which has increased from year to year. This research aims to find out what factors influence tourists' decisions to follow the Melukat tradition as a spiritual tourism attraction. These factors are based on the theory of Kotler and Keller (2009), factors including culture, social factors, personal factors and psychological factors which become benchmarks for tourist behavior or decisions. The research method used is quantitative. The data collection techniques used were questionnaires and observation. The sampling technique used was Accidental Sampling, with a sample size of 100 respondents. The data analysis techniques used are simple regression, partial test (t test), simultaneous test (f statistical test). The results show the factors that influence tourists' decisions to carry out the melukat tradition or ceremony are cultural factors, social factors, personal factors, and psychological factors. The most dominant factors are influenced by psychological factors and those that are not dominant are cultural factors.